PERAN GURU DALAM MENGEMBANGKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1A SD NEGERI 2 PLIKEN - Restiana Magitasari; Cicih Wiarsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Early reading skills are a fundamental foundation learning, and students must master them. The first-grade students of class 1A at SD Negeri 2 Pliken exhibit diverse reading abilities, with notable improvement observed among students who previously could not read, now reading better. The activity and creativity of the first-grade teacher significantly influence the fluency and accuracy of children’s reading at the initial learning stage. Therefore, this study aims to determine the role of the teacher in developing the early reading skills of class 1A students at SD Negeri 2 Pliken, along with the supporting and inhibiting factors. The research are the principal, class teacher, and students of class 1A at SD Negeri 2 Pliken. Data collection techniques include observation, interviews, and documentation. The result of this study indicate that the role of the class 1A teacher at SD Negeri 2 Pliken in developing early reading skills is quite effective. The teacher’s roles include organizer, mediator, facilitator, and motivator. As an organizer, the teacher successfully implements a 15-minute literacy habit before lessons begin. As a mediator, the teacher seeks engaging reading materials for students. As a facilitator, the teacher creates an attractive reading corner for students. As a motivator. The teacher supports and appreciates students brave enough to read in front of their peers. The supporting factors include good cooperation between teachers and students, students’ parents, school policies, learning media, and the availability of reading books. The inhibiting factors are internal challenges within the students and time constraints.